Percutaneous Coronary Intervention in Saphenous Vein Grafting Failure: A Case Report - Laksono, Sidhi; Syahirah, A Tenri (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Bypass graft surgery for coronary arteries is an essential therapy for those diagnosed with multivessel arterial stenosis, particularly in patients with diabetes. Internal thoracic artery grafts are the most suitable choice for revascularizing severe arterial disease due to their durability and longevity. However, complete revascularization is challenging to achieve only with grafts from the artery, which means it requires using saphenous vein grafts (SVGs). Unfortunately, saphenous vein grafts lack the same level of structural integrity, and their malfunction is associated with substantial negative cardiac consequences and higher death rates. In this case, the patient is an 80-year-old male suffering from CABG surgery 13 years prior. He had cold sweats and frequent chest pain that shot up his back. Diabetes, hypertension, and smoking were among his risks. Electrocardiography showed significant ischaemia, and echocardiography indicated mild diastolic dysfunction and impaired left ventricular systolic function with a 48% ejection fraction. Laboratory results indicated increased troponin I production and random blood glucose. After percutaneous coronary intervention and DES implantation into the diagonal saphenous vein grafts, the patient was given beta-blockers, nitrates, and statins as dual antiplatelet treatment.